The Pedunculopontine Tegmental Nucleus as a Motor and Cognitive Interface between the Cerebellum and Basal Ganglia - Mori, Fumika; Okada, Ken-ichi; Nomura, Taishin; Kobayashi, Yasushi (Frontiers in Neuroanatomy, 2016)
As an important component of ascending activating systems, brainstem cholinergic neurons in the pedunculopontine tegmental nucleus (PPTg) are involved in the regulation of motor control (locomotion, posture and gaze) and cognitive processes (attention, learning and memory). The PPTg is highly interconnected with several regions of the basal ganglia, and one of its key functions is to regulate and relay activity from the basal ganglia. Together, they have been implicated in the motor control system (such as voluntary movement initiation or inhibition), and modulate aspects of executive function (such as motivation). In addition to its intimate connection with the basal ganglia, projections from the PPTg to the cerebellum have been recently reported to synaptically activate the deep cerebellar nuclei. Classically, the cerebellum and basal ganglia were regarded as forming separated anatomical loops that play a distinct functional role in motor and cognitive behavioral control. Here, we suggest that the PPTg may also act as an interface device between the basal ganglia and cerebellum. As such, part of the therapeutic effect of PPTg deep brain stimulation (DBS) to relieve gait freezing and postural instability in advanced Parkinson’s disease (PD) patients might also involve modulation of the cerebellum. We review the anatomical position and role of the PPTg in the pathway of basal ganglia and cerebellum in relation to motor control, cognitive function and PD.